(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Globally, the demand of sustainable development is increased; the industry’s basic challenge is to fully extract the advantages with diminished use of Portland cement. This can be possible if we use blended cement and recyclable material in concrete which not only reduce cost of construction but also reduce pollution.An experimental program was planned in which one lean concrete mix which did not include any percentage of rice husk ash and rubber fibres and fifteen different mixes with different combinations of Rice Husk Ash and steel Fibres were prepared. Cubes and cylinder specimens were casted to obtain the different physical properties of sixteen concrete mixes with 0%, 7.5%, 12.5%, 17.5% and 22.5% of rice husk ash as to replace some part of cement and 0%, 3%, 6% and 9% of steel fibers as to replace some part of natural coarse aggregates. The cube specimens, cylindrical specimens and beam specimens will be tested after the recommended curing time of curing period of 7 days and 28 days respectively.